Use of online applications in maintaining MSMEs performance during the COVID-19 pandemic - Nurlinda, Nurlinda; Sinuraya, Junus; Asmalidar, Asmalidar; Hassan, Rahayu; Supriyanto, Supriyanto (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
This study aims to see whether there are differences in sales made by offline/conventional and online MSMEs to discover alternative media transactions to survive and increase sales during the COVID-19 period. This research is an exploratory study on MSMEs players who sell Rujak Sentir at Simpang Jodoh, Percut Sei Tuan, Deli Serdang District, Indonesia. The data source in this research is primary data by collecting data using a questionnaire on 50 samples of Rujak Sentir MSMEs merchants. Data were analyzed using statistical descriptive analysis of the Wilcoxon Signed Rank Test. The final analysis of data shows that the apply of online applications can be an alternative for MSMEs in maintaining and improving performance throughout the COVID-19 pandemic. The usage of this research practice is to give input to related parties regarding other options that can be utilized by enterprises throughout the Coronavirus widespread so that in the future, MSMEs are ready to face uncertainties that arise due to external factors. In addition to this, this research will be a recommendation regarding technical guidance that can be carried out by the local government in fostering MSMEs.